Fostering elementary school English teachers' professional identity through artifacts of practice. Issue 4 (4th July 2018) - Chien, Chin-Wen
ABSTRACT: Documents, interviews, and observation notes were used to analyze 19 Taiwanese elementary school English teachers' professional identity construction through artifacts and tools. The conceptual framework was adopted from Wetzler's (2010) Teacher Learning and Performance and Wertsch's (1998) three conceptual terms of artifacts. The study concluded two findings. First, the power and authority of the artifacts and tools referenced by participants also helped them to construct their professional identities. Second, the affordance of artifacts and tools led English teachers to exercise their reflective practice.